Challenges and advances in mycobacterial molecular typing - Minh Phuong Trinh; 신민경 (Annals of clinical microbiology, 2025)
Mycobacterium tuberculosis (MTB) and nontuberculous mycobacteria (NTM) presentdistinct clinical and epidemiological challenges and thus require tailored genotypingapproaches. MTB is a globally transmissible pathogen for which diagnostic and surveillanceinfrastructures are well defined, whereas NTM infections are environmentally acquired,taxonomically diverse, and increasingly prevalent among vulnerable populations. Moleculargenotyping is indispensable for both pathogen groups, supporting outbreak investigationand drug resistance prediction for MTB and species-level identification and relapse-versusreinfection distinction for NTM. In this review, the evolution of strategies for genotypingmycobacteria are outlined, and traditional techniques (e.g., spoligotyping and mycobacterialinterspersed repetitive unit–variable number tandem repeat genotyping) and advancedmethods (multilocus sequence typing and whole-genome sequencing) are compared. Wehighlight the divergent drivers of genotyping between MTB and NTM, examine key technicaland interpretive challenges, and discuss how cross-learning between these two fieldscan accelerate innovation. Emerging technologies such as portable sequencing platforms,artificial intelligence-assisted analysis, and curated genomic databases are expanding accessto high-resolution genotyping. However, significant gaps remain, particularly in standardizingNTM genomic analyses and integrating genotypic data into global surveillance systems. Byexploring the intersections between MTB and NTM molecular epidemiology, a synergisticpathway for more precise, accessible, and effective mycobacterial genotyping is highlighted. KCI Citation Count: 0